Information Literacies of PhD Students in the Health Sciences: A Review of Scholarly Articles (2009 - 2018) - Nylander, Elisabeth; Hjort, Margareta (Evidence Based Library and Information Practice, 2020)
Objective – Doctoral studies offer a unique phase in the development and legitimization of researchers, in which PhD students shift from the consumption to the production of knowledge. If librarians are to support this process in an evidence based manner, it is essential to understand the distinct practices of this user population. While recent reviews exist concerning the information behaviours of graduate students and researchers, there is little knowledge synthesis focused on the information literacies of PhD students in specific disciplines. The aim of this article is to explore the depth and breadth of recent evidence which describes the information literacies of students pursuing a doctoral degree in the health sciences.Methods – Strategic searches were performed in databases, hand-searched key journals, and reference lists. Records were screened independently by both authors based on pre-determined criteria. General trends within the literature were mapped based on the extraction of the following data: geographic location, population, study aims, and method of investigation. Further analysis of the articles included charting the academic disciplines represented, summarizing major findings related to PhD students in health sciences, and which databases indexed the relevant articles.Results – Many studies fail to treat doctoral studies as a unique process. PhD students are often grouped together with other graduate students or researchers. Studies tend to be based on small populations, and the number of PhD students involved is either unclear or only equals a few individuals within the entire group of study. In addition, of the limited number of studies which focus exclusively on PhD students, few conduct explicit examination of information practices in the health sciences. The result is that this user group is underrepresented within recent journal publications.Conclusion – This review highlights the need for more primary, in-depth research on the information literacies of PhD students in the health sciences. In addition, librarians are encouraged to share their knowledge in scholarly publications which can reach beyond their own professional circles.